2020
DOI: 10.3390/ijerph18010043
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and Maintenance of a Community-Based Intervention for Refugee Youth Reporting Symptoms of Post-Traumatic Stress: Lessons from Successful Sites

Abstract: Over the last few years there have been attempts to scale-up Teaching Recovery Techniques (TRT), a community-based group intervention for refugee youth reporting symptoms of post-traumatic stress, across Sweden using the distribution network pathway model. This implementation model allows for quick spread, but only for a low level of control at local sites. This study explores factors and agents that have facilitated the implementation and maintenance of the community-based intervention in successful sites. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Availability and accessibility of mental health services were concerns in all countries. Demand outstrips supply of mental health resources, with insufficient numbers of mental health workers and/or services reported in Egypt, Jordan 38 – 40 , Türkiye, Switzerland 41 44 , Sweden 45 , 46 , Germany 47 50 , and in Lebanon:…”
Section: Resultsmentioning
confidence: 99%
“…Availability and accessibility of mental health services were concerns in all countries. Demand outstrips supply of mental health resources, with insufficient numbers of mental health workers and/or services reported in Egypt, Jordan 38 – 40 , Türkiye, Switzerland 41 44 , Sweden 45 , 46 , Germany 47 50 , and in Lebanon:…”
Section: Resultsmentioning
confidence: 99%
“…Given these circumstances, TRT facilitators have a great responsibility in facilitating attendance and progression throughout the intervention. Qualitative evaluation of the factors that have aided the implementation and maintenance of TRT delivery revealed that group facilitators should go to where the youth are, rather than expect them to come to where TRT is offered [ 47 ]. When URM are not residing together, one may need to consider other strategies, such as offering TRT in the school setting or online delivery of TRT.…”
Section: Discussionmentioning
confidence: 99%
“…The complexity of post-migration-related concerns among traumatized refugees highlights the growing necessity for contextual information on recovery techniques and clinical interventions among these individuals that are essential to their survival [7]. This will primarily emphasize both mental and physical health, as well as enhance general health behaviour, daily life functioning, and psycho-social adjustment [8,9]. It is equally relevant to establish that the fundamental requirements of refugees, such as shelter, regular meals, protection from harm as well as the ability to work and earn income are crucial and inevitable in tackling the general wellbeing of refugees in trauma therapy and care [10].…”
Section: Introductionmentioning
confidence: 99%